The Nutritional Value of Fermented Banana Peels using Different Levels of Palm Sap - Theresia Nur Indah Koni; Tri Anggarini Yuniwaty Foenay; Cystke Sabuna; Eny Rohyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
Banana peels are banana processing wastes that can be used as poultry feedstuff, but bacause of its high crude fiber content, so to reduce the high crude fiber content it need processing such as fermentation. Fermentation process requires soluble carbohydrates such as palm sap. This research aimed to evaluate the effect of different levels of palm sap as an additive on the nutrient composition of banana peels. An experimental method was used in this research with a completely randomized design consisted of five treatments and four replications. The five treatments were banana peel with 0%, 12,5%, 15%, 17,5% and 20% addition of palm sap. The parameters measured were dry matter, crude protein, crude fiber, fat, and ash content. Data were analyzed by analysis of variance and followed by Duncan's Multiple Range Test. The results showed that increasing levels of palm sap reduced the content of dry matter, crude fiber and crude fat, increased crude protein content, but it did not affect the ash content of banana peels. The use of 20% of palm sap produced the highest protein content and the lowest crude fiber content.